2018
DOI: 10.4103/aer.aer_6_18
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal instillation of bupivacaine and ropivacaine for postoperative analgesia in laparoscopic cholecystectomy

Abstract: Background:Intraperitoneal instillation of local anesthetics in laparoscopic cholecystectomy (LC) has been used to reduce postoperative pain and to decrease the need for postoperative analgesics.Aims:This study aimed to compare intraperitoneal instillation of bupivacaine and ropivacaine for postoperative analgesia in patients undergoing LC.Settings and Design:This was a prospective, randomized, double-blind study.Materials and Methods:After obtaining ethical committee's clearance and informed consent, sixty pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…It was similar to the result from Rosero and Joshi [14], who found that 11.8% unplanned readmission patients had the complaint of wound pain. Rahimzadeh et al [25] and Sharan et al [26] injected ropivacaine or bupivacaine in the Trocar site to reduce post-operative wound pain. Hamad et al [27] combined adrenaline and bupivacaine to inject in all ports to reduce the post-operative pain.…”
Section: Discussionmentioning
confidence: 99%
“…It was similar to the result from Rosero and Joshi [14], who found that 11.8% unplanned readmission patients had the complaint of wound pain. Rahimzadeh et al [25] and Sharan et al [26] injected ropivacaine or bupivacaine in the Trocar site to reduce post-operative wound pain. Hamad et al [27] combined adrenaline and bupivacaine to inject in all ports to reduce the post-operative pain.…”
Section: Discussionmentioning
confidence: 99%
“…While many studies have been conducted with regards to their use in this context, the benefits of adding antibiotic solutions to the septic abdominal cavity remain unclear, and its pharmacological-clinical effectiveness remains unknown [22]. Other types of solutions such as anesthetics, more commonly, bupivacaine, have been utilized as post-surgical analgesia with varying levels of success [23-24]. Hypochlorous acid is also utilized as an instillation fluid to reduce abdominal fluid viscosity, thus increasing the removal of inflammatory ascites and septic material in the abdominal cavity [25].…”
Section: Discussionmentioning
confidence: 99%
“…Examples of some intraperitoneally used local analgesics are lignocaine [19,20], bupivacaine [21] meperidine [22], and recently, ropivacaine [23][24][25][26][27]. The latter has demonstrated a superior cardioprotective effect compared to bupivacaine [28][29][30], while providing longer pain relief and reducing opioid usage [31][32][33].…”
Section: Introductionmentioning
confidence: 99%